Comparison between the treatment area of electrode used for radiofrequency ablation of liver cancer focusing on 15G cooled-tip and CWT electrode - Kim, Hyun-Jin (Pak J Med Sci, 2016)
OBJECTIVES: To analyze the comparison between the treatment area of 15Gage internally cooled electrodes and 17 Gage Cool Wet-tip(CWT) electrodes. They are manufactured to broaden treatment area of the tumor in the radiofrequency ablation of hepatocellular carcinoma(HCC). METHODS: The study was designed for 62 patients with a mean age of 61, ranging from 44 to 87 years. The sample comprised of patients who used 15 G internally cooled electrodes and 17 G CWT electrodes respectively. Computed tomography (CT) images obtained after the procedure were observed, however, for the ablation lesion, the volume was determined by measuring complete necrotic tissue that did not contrast enhancement in the image. RESULTS: The treatment area of the tumor after radiofrequency ablation was 17.26±6.02 in the CWT, which was bigger than 15G. The treatment area ratio of the treatment before or after was significant at 581.85±339.56 in the CWT. After radiofrequency ablation, the treatment area got bigger, as 15G electrodes went toward CWT electrodes. Treatment area per electrode was 1.34 times higher in CWT than in 15G while the treatment area ratio of the treatment before or after was 1.001 times higher in the CWT than 15G. CONCLUSIONS: Ablation is more common for the safety margin in stable tumor and CWT type electrodes that can make larger ablation to reduce the number of times ablation is required for residual tumor and it decreases recurrence, ablation time and reoperation. Therefore it is considered t useful to reduce patients’ pain.